Thermal-exergetic behavior of triangular vortex generators through the cylindrical tubes. (April 2020) - Pourhedayat, Samira; Pesteei, Seyed Mehdi; Ghalinghie, Hamed Ebrahimi; Hashemian, Mehran; Ashraf, Muhammad Aqeel
Highlights: Energy/exergy analysis of the new arrangements of vortex generator are studied. New geometric characteristics of triangular winglet have been numerically evaluated. The effect of winglet-plate angle and latitudinal pitch were found significant. Nusselt number, friction factor, R3 performance and J factor were discussed. Abstract: In this paper, new arrangements of triangular winglet as a turbulator are numerically studied through a cylindrical tube. Triangular winglets are commonly placed on one side of a rectangular plate and inserted inside the tube. However, in present work, the winglets are located on both sides of the rectangular plate to further enhance the thermal performance of the fluid flow through the tube. Both backward and forward configurations of the winglets are analysed. Moreover, despite the importance of "latitudinal pitch of the winglets" and "winglet-plate angle" no investigation has been evaluated these parameters which will be evaluated in this work. Moreover, as no exergetic evaluation has been performed for triangular vortex generator, exergetic behavior of the triangular winglet is analysed as well. The impacts of all said factors on thermal, frictional and exergetic specifications of fluid-flow under the constant wall-temperature are investigated. The results showed that forward configuration provides higher thermal performance. Moreover, smaller longitudinal pitch and aspect ratio can provide stronger heat transfer rate through the tube. However, latitudinal pitch showed an extremum point which means that the winglet should not be very close to the wall-side or central-side of the tube. Among the tested latitudinal pitches (among 0 and 40 mm), the pitch of 20 mm showed the maximum enhanced heat transfer. Besides, the behavior of Nu number for smaller aspect ratios (below the 60°) is different from higher degrees (more than 60°).